A ameaça ao direito à educação pelas reformas neoliberais e ideologias da desescolarização nos países sul-americanos - Fávero, Lucas Antonio (2021)
It investigates the threats to the right to education by neoliberal schooling policies, promoted by international and national bodies and organizations, aiming at decreasing State funding in the provision of public and free education. The general objective is to verify how the right to education has been weakened by neoliberal orientations, in order to make state action more flexible, allowing other unschooled methods of education. The specific objectives are: 1) To verify, in the constitutions of the countries of South America, if the right to education is part of the guarantees given by the States; 2) Analyze the direction given by international organizations for the creation and application of educational policies, taking Chile and Brazil as examples; 3) Understand the ideologies of unschooling defended by neoliberal authors. To meet the objectives, it uses the historical-dialectical materialist method and analyzes the constitutions of the South American countries, in order to see if mandatory education is a positive guarantee guaranteed by the legislator, and the State is responsible for its promotion. In addition, it presents a survey of the main documents produced by international organizations influencing public education policies: World Bank, International Monetary Fund, Organization for Economic Cooperation and Development, United Nations Educational, Scientific and Cultural Organization. It concludes that the application of the neoliberal model in Chilean education caused privatization and segregation, transforming the executing State into an evaluating State, producing the privatization of education. The same path is followed in other South American countries, where the school has been gradually replaced by standardized tests that allow education at home, according to the neoliberal model of the State.